Materials for the aquatic hemiptera (Heteroptera) fauna of the Charyn State National Natural Park - Esenbekova, P.А.; Altynbek, Т.О.; Zhaksybayev, М.B. (KU publ., 2020)
As a result of research in 2019, 21 species out of 7 families of Hemoptera were identified in the Charyn State National Natural Park. From these species composition, 14 species are zoophages; the remaining 7 species are zoophytophages. Identified all species have a wide selection of hunting objects, feed on aquatic invertebrates, including regulating the numbers of blood-sucking mosquito larvae (Culicidae). The main purpose of the research is to identify the species composition of the aquatic hemiptera Charyn State National Natural Park. Here, a systematic special study of the fauna of the aquatic hemiptera was not carried out before. Only 2 articles on half-winged animals have been published. Aquatic Hemiptera insects by species diversity and environmental features are one of the groups most suitable for its use in various environmental studies; they are well adapted to various environmental conditions.
Шарын мемлекеттік ұлттық табиғи паркіндегі су жартылайқаттықанаттылар (Heteroptera) фаунасы
Материалы к фауне водных полужесткокрылых (Heteroptera) Чарынского государственного национального природного парка
Keywords: fauna; Heteroptera; Charyn State National Natural Park; family; larva